Analysis philosophical and legal concept of justice in the philosophy of law - Пашаева, Антига (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
One of the issues "justice" analyzed in the philosophy of law and these theme is the basis of jurisprudence. The justice, as one of the most important properties of morality and also reflects its superior attributes. According to the philosophers, the concept of justice is divided into several categories and development of these categories based right and laws. The meaning of justice relationship principles of the laws and that do not reflect the meaning of justice, will be available word. The study have been analyzed of ancient Greek thinkers in outlook and subsequently the thoughts of justice and it was concluded at that time, justice in relation to a person the attributes of its superior, it was adopted as the basis of respecting the right of others. If a person shows irresponsibility to others forcing him to remorse sense of justice. Unlike them, Hegel the meaning of justice, the state coordinates. According to him, the principles of justice are linked to the requirements of the state, among the principles “being” and “must being” there is no difference. Justice, regulates the legal rules and regulate them in accordance with the structure. The purpose of justice, there are signs that any person whether you are entitled to in compliance with the law. The person in front of the law and fulfilling the duties required by law, but also holy count its principles and must accept any issue related to law. İn the article, by reference to the theory of philosophers and lawyers, studing meaning of justice and meaning of right and also analyzed social aspects.